Effectiveness of an Instructional Program on Practice of Patients’ Safe Measures Post Implantable Cardioverter Defibrillator (Medical Forum Monthly, 2024)
Objective: To ascertain the effectiveness of the instruction program on patients' practices about safe measures post implantable cardioverter defibrillator.Study Design: A quasi-experimental studyPlace and Duration of Study: This study was conducted at the Ibn–Al-Bitar Specialized Center, Baghdad city from 19th May 2023 to 16th February 2024.Methods: Pre-test and post-test approaches are used for the groups (control and study). Sixty patients participated (30) in each group. Date was collected through the use of constructed program and instruments for the safe measures after ICD implantation, the study instrument included three sections: socio-demographic characteristics, medical information, and patients' practices regarding safe measures post-ICD implantation.Results: The study group demonstrated a fair level of practice in safe activity and a good level of electrical devices, and magnetic devices domains, while in the control group, the domains were within fair level except the electrical devices were at poor level at pre-program. However, after the program implementation, the majority of study group had adequate total practice scores on the contrary the control group remained at a fair level.Conclusion: The practices of patients regarding safe measures post ICD was fair level for both groups. After implementing the instructional program, the study members' practices increased to a respectable level. While the practices of the control group remained unchanged over the testing period.